2011
DOI: 10.1007/s11356-011-0649-3
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation and microbial community analysis of the simulated river bioreactor for contaminated source water remediation

Abstract: Artificial enhancement via the combination of sediment discharging and influent velocity gradient increasing could enhance the biofilm formation and autotrophic AOB enrichment in oligotrophic niche.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…Figure A presents the NH 4 + ‐N removal performance in the reactors. NH 4 + ‐N removal efficiency is an important indicator of the success of biofilm formation . With an influent NH 4 + ‐N concentration of 4.49 ± 0.73 mg L −1 , the control reactor R 0 required almost 1 month to achieve more than 80% NH 4 + ‐N removal efficiency, which was similar to a previous study.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Figure A presents the NH 4 + ‐N removal performance in the reactors. NH 4 + ‐N removal efficiency is an important indicator of the success of biofilm formation . With an influent NH 4 + ‐N concentration of 4.49 ± 0.73 mg L −1 , the control reactor R 0 required almost 1 month to achieve more than 80% NH 4 + ‐N removal efficiency, which was similar to a previous study.…”
Section: Resultssupporting
confidence: 82%
“…Results suggested that the reactors with pomelo peel (R 1 ) and durian peel (R 3 and R 4 ) both had an obviously shorter lag stage for TN removal than that of the reactor with rice husk (R 2 ), which was similar to the lag stage in NH 4 + ‐N removal. The main reason for the poor nitrogen removal performance in the lag phase was attributed to an unformed biofilm on the carrier . Average TN removal efficiencies in the stable stage were 80.8 ± 11.7% (R 1 ), 58.4 ± 12.3% (R 2 ), 82.6 ± 6.2% (R 3 ) and 91.5 ± 5.7% (R 4 ), with average effluent TN concentrations of 1.18 ± 0.76 mg L −1 (R 1 ), 2.73 ± 0.85 mg L −1 (R 2 ), 1.08 ± 0.42 mg L −1 (R 3 ) and 0.56 ± 0.42 mg L −1 (R 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Therefore, it is important to ensure that the elemental composition of the support media is compatible with the microbial community. The intensity of photoelectrons as a function of the binding energy for two support materials (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Wastewater treatment capability of fixed biofilm reactors depends on microbes and carrier media . It have been reported that properties of biofilm supporting media influence early microbial attachment and its growth, thereby affecting the efficiencies of the bioreactors . Motta also reported that microbial growth supporting media is one of the critical factors by providing exterior to microbial attachment, growth and contact with pollutants for removal.…”
Section: Discussionmentioning
confidence: 99%